Diet of adults and cubs of Lycalopex gymnocercus in Pampas grassland: A validation of the Optimal Foraging Theory? - Castillo, Diego Fabián (2011)
We compared the diet of adult Pampas foxes (Lycalopex gymnocercus) and their cubs in a Pampas grassland area of Argentina by analysing 152 scats (adults: 92, cubs: 60). We used an Index of Relative Importance (IRI) to determine the contribution of prey items to the diet. IRI scores for rodents, hares and birds were higher for cubs, whereas adults consumed grasshoppers and larvae more often than cubs did. Fruits and carrion of ungulates were consumed only by adults. Both the number of items per scat and diet diversity were smaller for cubs than adults. We conclude that the Pampas fox behaves as a typical central place forager, with fruits and insects being probably consumed on the spot (with low foraging costs) and rodents, birds and hares being brought to the den for the cubs. © Finnish Zoological and Botanical Publishing Board 2011.